Whether to prescribe calcium and vitamin D: arguments pro and contra - N. V. Toroptsova (Медицинский совет, 2013)
Today we know that calcium and vitamin D are the essential factors of health of the whole organism. A balanced intake of calcium and vitamin D is a basis for the formation and maintenance of healthy bone, while their insufficiency is a risk factor for osteoporosis and fractures.